SYNTHESIS AND CHARACTERIZATION OF COMPOSITE ZEOLITE-RESIN POLYMETHACRYLATE - Yusuf Nampira (Jurnal Zeolit Indonesia, 2008)
Composite of Zeolite-resin polymethacrylate have been made with various compositions of zeolite on composite. The composite were made by homogenous mixture of zeolite powder with powder of tetrahidro furfuryl methacrylate, methacrylate polymerization which was conducted by pasta phases with mixing 1 ml mixture solution of tetrahidro furfuryl methacrylate and hydroxy propyl methacrylate. A big part of zeolite in product composite was in the polymer solution phase. The balance between supporting material and matrix material around the zeolite on composite of zeolite-resin polymethacrylate obtained on the fraction of zeolite in the composite between the 46.67% of weight up to 70% of weight. Strength and hardness of zeolite-resin polymethacrylate depends on balance between zeolite and resin polymethacrylate. The optimum hardness of this composite reaches value of 29,7 N/Ä±m2, which obtained from composite that have a fraction zeolite 46,67% of weight.